2004
DOI: 10.1093/jxb/erh044
|View full text |Cite
|
Sign up to set email alerts
|

A transgene encoding a blue-light receptor, phot1, restores blue-light responses in the Arabidopsis phot1 phot2 double mutant

Abstract: Phototropins (phot1 and phot2) are suggested to be multifunctional blue-light (BL) receptors mediating phototropism, chloroplast movement, stomatal opening, and leaf expansion. The Arabidpsis phot1 phot2 double mutant lacks all of these responses. To confirm the requirement of phototropins in BL responses, the Arabidopsis phot1 phot2 double mutant was transformed with PHOT1 cDNA and the phenotypic restoration was analysed in the transformants. It was found that all BL responses were restored, although differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 17 publications
4
60
0
1
Order By: Relevance
“…It has been shown that both the stomatal pore of leaf epidermal peels of the phot1 phot2 (Kinoshita et al, 2001) and cry1 cry2 (Mao et al, 2005) double mutants of Arabidopsis and the stomatal conductance of intact phot1 phot2 leaves (Doi et al, 2004) have severely impaired responses to blue light added to a background of red light. Based on these observations, it would be reasonable to predict that phot and cry are the receptors of the blue light-specific system involved in stomatal opening (although the role of cry had already been challenged; Shimazaki et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that both the stomatal pore of leaf epidermal peels of the phot1 phot2 (Kinoshita et al, 2001) and cry1 cry2 (Mao et al, 2005) double mutants of Arabidopsis and the stomatal conductance of intact phot1 phot2 leaves (Doi et al, 2004) have severely impaired responses to blue light added to a background of red light. Based on these observations, it would be reasonable to predict that phot and cry are the receptors of the blue light-specific system involved in stomatal opening (although the role of cry had already been challenged; Shimazaki et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In isolated epidermal peels of Arabidopsis (Arabidopsis thaliana) leaves, the blue light-induced promotion of the aperture of the stomatal pore is severely impaired in the phototropin1 phototropin2 (phot1 phot2) double mutant (Kinoshita et al, 2001) and the cry1 cry2 mutant (Mao et al, 2005). Furthermore, stomatal conductance fails to respond to blue light in intact leaves of the phot1 phot2 mutant (Doi et al, 2004). Since cry (Cashmore et al, 1999) and phot (Huala et al, 1997;Kagawa et al, 2001) are blue light photoreceptors, they could be directly involved in the perception of the blue light signal inducing stomatal aperture.…”
mentioning
confidence: 99%
“…The stomatal aperture in the abaxial epidermis was measured by microscopic examination (Eclipse TS100; Nikon) 11 . Stomatal conductance and photosynthetic CO 2 assimilation were determined using a gas-exchange system (LI-6400, Li-Cor) 18 .…”
Section: Methodsmentioning
confidence: 99%
“…We generated antibodies against the C-terminal region and phosphorylated Ser-348 of BLUS1 by immunizing rabbits with recombinant GST-BLUS1 (K294-G487) and a synthetic phospho-BLUS1 peptide (KNRRIpSGWNF), respectively. Antibodies against phot1, phot2 and H þ -ATPase were described previously 12,18,19 . Phosphorylation levels of phot1 and the H þ -ATPase were determined by protein blotting using 36).…”
Section: Methodsmentioning
confidence: 99%
“…This response has been shown to involve the activation of a plasma membrane H 1 -ATPase (Kinoshita and Shimazaki, 1999), although the steps leading up to this activation are not clear. The receptor for this response has yet to be identified unequivocally, and there is evidence supporting both zeaxanthin Talbott et al, 2003) and phototropins Doi et al, 2004) for this role. The RL response is also poorly understood, but many data suggest the involvement of guard cell photosynthetic processes.…”
mentioning
confidence: 99%